2019
DOI: 10.1111/1750-3841.14758
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Shelf Life Estimation of Novel Fortified Blended Foods Under Accelerated and Real‐Time Storage Conditions

Abstract: Fortified blended foods (FBFs), a staple of food aid around the world, must maintain desirable characteristics for long periods of storage. This study estimated the shelf life of FBFs, including a traditional FBF (nonextruded corn soy blend plus [CSB+]) and 13 novel extrusion cooked FBFs. All products were stored under accelerated and real‐time environments (real time = 30 °C and 65% relative humidity [RH], accelerated = 50 °C and 70% RH based on a Q10 factor of 2). Products were made into porridges and evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…As previously mentioned, the extruded products containing higher amount of lipids were more bitter ( p ≤ 0.05) because of the high possibility of having more degraded lipids. However, it must be noted that the lipids certainly were not degraded enough to produce marked changes in shelf-life [17]. Phenolic compounds, which can be found in sorghum, are responsible for the bitterness of many similar foods and may cause a negative effect on products’ acceptability [35,37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, the extruded products containing higher amount of lipids were more bitter ( p ≤ 0.05) because of the high possibility of having more degraded lipids. However, it must be noted that the lipids certainly were not degraded enough to produce marked changes in shelf-life [17]. Phenolic compounds, which can be found in sorghum, are responsible for the bitterness of many similar foods and may cause a negative effect on products’ acceptability [35,37].…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has shown that various types of extruded FBFs made with sorghum or corn and cowpea or soy are at least as preferred as CSB+ by children in Tanzania [16]. In addition, data has shown that the shelf-life of such products is generally 24 months or greater [17], far exceeding the required shelf-life for such products.…”
Section: Introductionmentioning
confidence: 99%
“…Such numbers of highly trained panelists have been shown to be able to discriminate among samples better than larger panels of less trained panelists [40][41][42]. Similar panels have been used for other recent studies [43][44][45].…”
Section: Panelistsmentioning
confidence: 99%
“…Such numbers of highly trained panelists have been shown to be able to discriminate among samples better than larger panels of less trained panelists [39][40][41]. Similar panels have been used for other recent studies [42][43][44].…”
Section: Panelistsmentioning
confidence: 99%